Alarming and Calming: Opposing Roles of S100A8/S100A9 Dimers and Tetramers on Monocytes. Issue 36 (30th October 2022) - Russo, Antonella; Schürmann, Hendrik; Brandt, Matthias; Scholz, Katja; Matos, Anna Livia L.; Grill, David; Revenstorff, Julian; Rembrink, Maximilian; von Wulffen, Meike; Fischer‐Riepe, Lena; Hanley, Peter J.; Häcker, Hans; et al.
Abstract: Mechanisms keeping leukocytes distant of local inflammatory processes in a resting state despite systemic release of inflammatory triggers are a pivotal requirement for avoidance of overwhelming inflammation but are ill defined. Dimers of the alarmin S100A8/S100A9 activate Toll‐like receptor‐4 (TLR4) but extracellular calcium concentrations induce S100A8/S100A9‐tetramers preventing TLR4‐binding and limiting their inflammatory activity. So far, only antimicrobial functions of released S100A8/S100A9‐tetramers (calprotectin) are described. It is demonstrated that extracellular S100A8/S100A9 tetramers significantly dampen monocyte dynamics as adhesion, migration, and traction force generation in vitro and immigration of monocytes in a cutaneous granuloma model and inflammatory activity in a model of irritant contact dermatitis in vivo. Interestingly, these effects are not mediated by the well‐known binding of S100A8/S100A9‐dimers to TLR‐4 but specifically mediated by S100A8/S100A9‐tetramer interaction with CD69. Thus, the quaternary structure of these S100‐proteins determines distinct and even antagonistic effects mediated by different receptors. As S100A8/S100A9 are released primarily as dimers and subsequently associate to tetramers in the high extracellular calcium milieu, the same molecules promote inflammation locally (S100‐dimer/TLR4) but simultaneously protect the wider environment from overwhelming inflammation (S100‐tetramer/CD69). Abstract : Mechanisms restricting local inflammation and preventing systemic spreading of diseases are hardly understood. Release of S100A8/S100A9‐dimers at local sites of inflammation leads to monocyte activation via TLR4 while calcium‐induced S100A8/S100A9‐tetramer formation in the extracellular space mitigates monocyte dynamics via CD69. Thus, different quaternary structures of the same molecules promote inflammation locally (S100‐dimer/TLR4) but simultaneously protect systemic spreading of inflammation (S100‐tetramer/CD69).